Social interaction, co-Worker altruism, and incentives - Robert Dur; Joeri Sol (Center for Economic Studies and ifo Institute (CESifo), 2008)
Social interaction with colleagues is an important job attribute for many workers. To attract and retain workers, managers therefore need to think about how to create and preserve high-quality co-worker relationships. This paper develops a principal-multi-agent model where agents do not only engage in productive activities, but also in social interaction with their colleagues, which in turn creates co-worker altruism. We study how financial incentives for productive activities can improve or damage the work climate. We show that both team incentives and relative incentives can help to create a good work climate. We discuss some empirical evidence supporting these predictions.
Keywords: D86; J41; M50; 330; Social interaction; altruism; incentive contracts; co-worker satisfaction; Betriebsklima; Gruppenarbeit; Altruismus; Leistungsanreiz; Arbeitszufriedenheit; Agency Theory; Theorie